Ceramic composite diaphragm containing graphite layer and lithium battery
By coating the ceramic layer on both sides on the lithium battery separator and adding a graphite layer, the problem of insufficient thermal stability of lithium batteries at high temperatures is solved, the safety and circulation performance of the battery are improved, and the risk of explosion is reduced.
Patent Information
- Application Number
- CN201810792054.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2018-07-18
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2038-07-18
AI Technical Summary
The existing lithium battery separators lack thermal stability at high temperatures, which can easily lead to combustion and explosion, and the ceramic layer has poor conductivity to the battery, affecting the cycle life.
The ceramic layer is coated on both sides of the base film surface, and a graphite layer is added to the outer surface of the ceramic layer to form a ceramic composite separator to improve the thermal stability and electrical conductivity of the separator.
It significantly improves the thermal stability, wetting and safety of lithium batteries, reduces the internal resistance of the battery, extends the cycle life, and reduces the risk of explosion in the event of short circuit or impact.
Smart Images

Figure CN108963166B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a lithium battery diaphragm, in particular to a ceramic composite diaphragm containing a graphite layer and a lithium battery comprising the ceramic composite diaphragm. Background Art
[0002] As a new type of high-energy chemical power source, lithium-ion batteries can cause heat accumulation inside the battery due to the thermal effect of the battery system under conditions such as high temperature or high-efficiency charging and discharging, which can easily cause the lithium battery to burn and explode. Therefore, the safety of lithium batteries is the primary consideration. At the same time, in the field of new energy vehicles, the demand for lithium-ion batteries is increasing year by year, and the demand for large-capacity and high-power batteries is imminent. It is very urgent to develop lithium-ion batteries with high safety, good cycle performance / conductivity. Summary of the invention
[0003] The inventors of this application have conducted in-depth research on the advantages and disadvantages of the structure and components of existing lithium batteries. At present, most of them adopt a layer of ceramic coated on the surface of the base film to improve the thermal stability of the diaphragm, thereby improving the safety of lithium batteries. However, the thermal stability of the diaphragm prepared in this way is still limited, and the shrinkage is still large at high temperatures above 130°C, so the high temperature resistance still needs to be further improved. On the other hand, ceramics do not contribute to the conductivity of the positive and negative current collectors of the battery, and the diaphragm ceramic layer is not conducive to the deintercalation of lithium ions during the high current discharge of the lithium battery. The battery has a large internal resistance and is prone to the formation of lithium dendrites, which reduces the cycle life of the lithium battery. In addition, graphite is generally coated on the negative electrode sheet as the negative electrode active material, but the hardness of the negative electrode prepared in this way is relatively large, and there are disadvantages such as being difficult to wind and form, and easy to fall off when impacted by external forces. Therefore, it is necessary to further develop technologies that can improve the thermal stability, wettability and / or safety of the diaphragm.
[0004] In order to solve the above problems, the inventors of the present application, after various attempts, unexpectedly discovered that when two ceramic layers are coated on the surface of the base film and a graphite layer is further added, the resulting diaphragm can have improved thermal stability, wettability, safety and excellent battery charge and discharge cycle performance after being assembled into a battery, thereby completing the present invention.
[0005] One aspect of the present invention relates to a diaphragm, comprising:
[0006] Basement membrane;
[0007] First and second ceramic layers provided on both surfaces of the base film; and
[0008] First and second graphite layers are disposed on outer surfaces of the first and second ceramic layers.
[0009] Figure 1A separator according to one embodiment of the present invention is shown, comprising a base film 1, first and second ceramic layers 2 and 3 provided on both surfaces of the base film, and first and second graphite layers 4 and 5 provided on the first and second ceramic layers.
[0010] The base film can be any base film suitable for lithium batteries known in the prior art, for example, it can be a microporous film, a porous film or a non-woven film. The microporous film and the porous film can be a polyolefin film, for example, it can be a single-layer polyethylene (PE) or polypropylene (PP) diaphragm, or a polyethylene and polypropylene multilayer composite film (for example, a polypropylene / polyethylene double-layer film, a polypropylene / polypropylene double-layer film, a polypropylene / polyethylene / polypropylene three-layer composite film, etc.). The polyolefin base film can be prepared by unidirectional or bidirectional stretching using a wet or dry process, or prepared using a thermally induced phase separation method. The material and preparation method of the non-woven film are not particularly limited, for example, one or more selected from polypropylene, polyethylene, polyimide, polyamide, polysulfone, polyacrylonitrile, polyester, cellulose, polyetheretherketone, polyphenylene sulfide, polyacrylate, polyphenylamide, polyarylethersulfoneketone, aramid and aromatic sulfone can be used as a material, and one or more selected from meltblowing, spunbonding, wet papermaking, spunlace, needle punching, hot rolling, etc. can be used.
[0011] There is no particular limitation on the pore size and porosity of the base film, as long as it is suitable for use as a separator for a lithium battery. Generally speaking, the pore size is required to be in the range of 0.01 to 0.1 μm, such as 0.02 μm, 0.03 μm, 0.04 μm, 0.05 μm, 0.06 μm, 0.07 μm, 0.08 μm, 0.09 μm, etc. When the pore size is less than 0.01 μm, the lithium ion penetration capacity is too small; when the pore size is greater than 0.1 μm, the battery is prone to short circuit when dendrites are generated inside the battery. The porosity is generally between 20% and 80%, especially between 30% and 50%, such as 35%, 40%, 45%, 55%, 60%, 65%, 70%, etc.
[0012] There is no particular limitation on the thickness of the base film as long as it is suitable for use as a separator for a lithium battery. Generally, the thickness is 30 μm or less, for example, 3-20 μm or 3-16 μm, such as 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, etc.
[0013] The first and second ceramic layers can be formed by a method for forming a ceramic layer known in the art. Without being limited to any theory, by adding a ceramic layer on the base film, the thermal stability and mechanical properties of the diaphragm can be improved, and the wettability of the diaphragm to the electrolyte can be improved, thereby improving the rate performance and cycle performance.
[0014] In one embodiment, the first and second ceramic layers may each independently include ceramic particles, a binder, a thickener and a wetting agent, preferably substantially consisting of ceramic particles, a binder, a thickener and a wetting agent, wherein the content of the ceramic particles may be 60 to 90 wt%, preferably 70 to 85 wt%, for example, 72 wt%, 75 wt%, 78 wt%, 80 wt%, 82 wt%, 84 wt%, etc., based on the total weight of the ceramic layer, and the content of the binder may be 5 to 25 wt%, preferably 9 to 15 wt%. , for example, 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, etc., the content of the thickener can be 4-10wt%, preferably 5-8wt%, for example 5.5wt%, 6wt%, 6.5wt%, 7wt%, 7.5wt%, etc., the content of the wetting agent can be 0.01-5wt%, preferably 0.01%-2wt%, for example 0.05wt%, 0.1wt%, 0.2wt%, 0.5wt%, 0.8wt%, 1.0wt%, 1.5wt%, etc.
[0015] In one embodiment, the first and second ceramic layers are each independently a water-based ceramic layer, wherein the ceramic layer components are prepared into a water-based ceramic slurry, which is then coated on the base film and dried. The solid content of the slurry may be 10 to 70 wt%.
[0016] In one embodiment, the thickness of the first and second ceramic layers can be independently 0.5 to 10 μm, preferably 2 to 5 μm. For example, the thickness of the first and second ceramic layers 2 and 3 can be independently 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm or 5 μm, etc. When the thickness is less than 0.5 μm, the shrinkage may not change much compared with the base film, and the shrinkage improvement is not obvious; when the thickness is greater than 10 μm, the ceramic layer may be easy to fall off, and the air permeability of the diaphragm may increase significantly.
[0017] In the first and second ceramic layers, the ceramic particles refer to particles with a diameter between 0.1 and 5 μm, for example, particles with a diameter of 0.2 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1.0 μm, 1.5 μm, 2.0 μm, 2.5 μm, 3.0 μm, 3.5 μm, 4.0 μm, 4.5 μm. Preferably, the ceramic particles may be one or more selected from aluminum oxide, titanium oxide, magnesium oxide, magnesium hydroxide, boehmite, etc.
[0018] The binder is an organic polymer known in the art for bonding ceramics, and is used to bond ceramic particles into an integral layer. For example, it can be one or more selected from polymethyl methacrylate, polyvinylidene fluoride, styrene-butadiene latex, styrene-acrylic latex, polyvinyl alcohol, ethylene-vinyl acetate copolymer, polyacrylonitrile, polyurethane, polyacrylonitrile, polymethacrylic acid, acrylic acid-acrylate copolymer, etc.
[0019] The wetting agent is used to reduce the surface tension of the aqueous slurry and improve the wettability of the slurry on the surface of the base film. For example, it can be polyoxyethylene alkylamine, sodium butylnaphthalene sulfonate, sodium isopropylnaphthalene sulfonate, sodium arylnaphthalene sulfonate, sodium dodecylbenzene sulfonate or sodium alkyl sulfate, fatty alcohol polyoxyethylene ether, etc.
[0020] The thickener is used to adjust the viscosity of the aqueous slurry and improve the coatability of the slurry, and may be, for example, carboxymethyl cellulose (CMC), carboxyethyl cellulose, polyacrylamide, guar gum, polyethylene oxide, and the like.
[0021] The first and second graphite layers can be independently formed by a method for forming a graphite layer known in the art. Without being limited to any theory, by further adding a graphite layer, the interface resistance between the positive and negative electrode active material layers and the ceramic layer is reduced, the internal resistance of the battery is reduced, the loss of lithium ions during the deintercalation process is reduced, and the battery charge and discharge cycle performance is improved. In addition, due to the conductive properties of graphite itself, when the battery is subjected to external impact or short circuit, the graphite layer will expand the power tolerance range, reduce the risk of explosion or fire, and improve the safety performance of the battery.
[0022] In one embodiment, the first and second graphite layers each independently include graphite, a binder, a thickener and a conductive agent, preferably substantially consisting of graphite, a binder, a thickener and a conductive agent, wherein the content of graphite can be 60 to 95 wt%, preferably 75 to 85 wt%, for example, 65 wt%, 70 wt%, 78 wt%, 80 wt%, 82 wt%, 84 wt%, 90 wt%, etc., based on the total weight of the graphite layer, and the content of the binder can be 4 to 30 wt%, preferably 8 to 20 wt%, for example, 9 wt%. %, 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, 15wt%, 16wt%, 17wt%, 18wt%, 19wt%, etc., the conductive agent content can be 0.5-2wt%, preferably 0.5-1.5wt%, such as 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1.0wt%, 1.1wt%, 1.2wt%, 1.3wt%, 1.4wt%, etc., the thickener content is 0.5-10wt%, preferably 2-6wt%. For example, 2.5wt%, 3.0wt%, 3.5wt%, 4.0wt%, 4.5wt%, 5.0wt%, 5.5wt%, etc.
[0023] In one embodiment, the first and second graphite layers are each independently an aqueous graphite layer, wherein the graphite layer components are prepared into an aqueous graphite slurry, which is then coated on the ceramic layer and dried. The solid content of the slurry may be 20 to 60 wt%.
[0024] In one embodiment, the thickness of the first and second graphite layers may be independently 0.1 to 50 μm, preferably 20 to 40 μm. For example, the thickness of the first and second graphite layers 4 and 5 may be independently 20 μm, 25 μm, 30 μm, 35 μm, or 40 μm, etc. In the case where the thickness is less than 0.1 μm, the improvement effect may not be achieved, resulting in the same performance as the ceramic diaphragm; and in the case where the thickness is greater than 50 μm, the graphite layer may be powdered and easy to fall off.
[0025] In the first and second graphite layers, the graphite is not particularly limited and may be natural or artificial graphite, or may be modified graphite, for example, low swelling graphite.
[0026] There is no particular requirement for the particle size of graphite, but the preferred particle size is 10 to 30 μm, preferably 15 to 20 μm, for example, 11 μm, 12 μm, 13 μm, 14 μm, 16 μm, 17 μm, 138 μm, 19 μm, etc.
[0027] In the present invention, the low swelling graphite is a modified graphite with a layer of amorphous carbon coated on the surface of natural or artificial graphite. When low swelling graphite is used, the surface active structure of graphite is modified to avoid direct contact between graphite and electrolyte, making it difficult for electrolyte to damage the graphite layer structure, thereby reducing capacity attenuation caused by graphite swelling.
[0028] In the present invention, the low swelling graphite is a composite material of amorphous carbon coated natural or artificial graphite obtained by coating natural or artificial graphite with a polymer or asphalt as a coating material, and then pyrolyzing it. The polymer is, for example, a phenolic resin, an epoxy resin, PVDF and its copolymers (for example, polyvinylidene fluoride-co-hexafluoropropylene). In the manufacture of low swelling graphite, the mass ratio of the polymer or asphalt as an amorphous carbon precursor to the natural or artificial graphite can be 0.05 to 1:1, for example, 0.05 to 0.5:1.
[0029] There are no special requirements for the low swelling graphite suitable for the present invention, but it is preferred that the particle size D50 of the coated LSG is 18-24 μm; D90 ≤ 40 μm. Here, D50 and D90 refer to the average particle size of the largest particles when the cumulative distribution in the particle size distribution curve of LSG is 50% and 90%, respectively.
[0030] In the graphite layer of the present invention, the binder is an organic polymer known in the art for bonding graphite, which is used to bond the granular graphite particles into an integral layer. For example, the binder can be one or more selected from polymethyl methacrylate, polyvinylidene fluoride, styrene-butadiene latex, styrene-acrylic latex, polyvinyl alcohol, ethylene-vinyl acetate copolymer, polyacrylonitrile, and polyurethane.
[0031] In the graphite layer of the present invention, the conductive agent is used for lithium ion transmission. There is no particular limitation on the conductive agent, as long as it is a conductive agent commonly used in lithium batteries. For example, the conductive agent can be one or more selected from acetylene black, conductive carbon black, carbon fiber, and graphene.
[0032] The thickener is used to adjust the viscosity of the aqueous slurry and improve the coatability of the slurry, and may be, for example, carboxymethyl cellulose (CMC), carboxyethyl cellulose, polyacrylamide, guar gum, polyethylene oxide, and the like.
[0033] The diaphragm according to the present invention may further include an electrospinning layer, a heat-sealing layer, a nano flame-retardant layer, and the like.
[0034] Another aspect of the present invention relates to a method for preparing a membrane according to the present invention, comprising the following steps:
[0035] 1) Ceramic particles, a binder, a wetting agent and deionized water are uniformly mixed to obtain a water-based ceramic slurry.
[0036] 2) mixing graphite, binder, conductive agent and deionized water to obtain water-based graphite slurry,
[0037] 3) coating the aqueous ceramic slurry on both surfaces of the base film to form the first and second ceramic layers and then drying;
[0038] 4) The aqueous graphite slurry is applied onto the outer surfaces of the first and second ceramic layers to form the first and second graphite layers, respectively, and then dried to obtain a separator.
[0039] The above steps (1) and (2) are only used to distinguish the two operations, and do not represent the order of their operations. The two operations can be performed simultaneously or successively. The first and second ceramic layers and the first and second graphite layers are only used to distinguish the two layers, and do not mean their order.
[0040] In the above step 1), there is no particular limitation on the method for uniformly mixing ceramic particles, binder, wetting agent, and deionized water, as long as they are uniformly mixed, for example, a planetary mixer, a homogenizer, etc. can be used. In one embodiment, the ceramic particles and deionized water can be mixed, stirred at 20-40°C and a speed of 500-3000rpm / min for 0.5-2h, a binder is added, and stirring is continued for 0.5-1.5h under the same conditions, and then a wetting agent is added, and stirring is continued for 0.5-1h at the same temperature and 300-800rpm to obtain a water-based ceramic slurry. According to this method, it helps to reduce particle agglomeration and promote uniform mixing.
[0041] In the above step 2), there is no particular limitation on the method for uniformly mixing graphite, binder, conductive agent, and deionized water, as long as they are uniformly mixed, for example, a planetary mixer, a homogenizer, etc. can be used. In one embodiment, graphite, binder, and deionized water can be mixed and planetarily stirred at a temperature of 25 to 40°C, a rotation speed of 1000 to 2500 rpm / min, and a time of 0.5 to 2 hours; then a conductive agent is added, and the temperature is maintained at 25 to 40°C, and the stirring is performed at 800 to 2000 rpm / min for 20 minutes to 1.5 hours to obtain an aqueous graphite slurry. According to this method, it helps to reduce particle agglomeration and promote uniform mixing.
[0042] In the above step 3), the aqueous ceramic slurry in 1) can be coated on both sides of the base film by micro-gravure coating, and dried to obtain the first and second ceramic layers.
[0043] In the above step 4), the aqueous graphite slurry described in 2) can be coated on the outer surface of the aqueous ceramic layer and dried to obtain the first and second graphite layers.
[0044] There is no limitation on the drying method of the graphite layer and the ceramic layer as long as it is suitable for preparing the separator. For example, baking can be used.
[0045] The content of deionized water in the aqueous ceramic slurry and the aqueous graphite slurry is not particularly limited, as long as the final slurry is suitable for coating, and can be appropriately selected according to the coating method used. For example, based on the total weight of the slurry, the content of deionized water in the aqueous ceramic slurry can be 30 to 90 wt%; the content of deionized water in the aqueous graphite slurry can be 40 to 80 wt%.
[0046] The method for preparing a diaphragm according to the present invention may also include, as required, operations such as preparing an electrospinning layer, a heat-sealing layer, a nano flame-retardant layer, etc. The operations such as preparing the electrospinning layer, the heat-sealing layer, the nano flame-retardant layer, etc. may be performed using conventional operations for preparing these layers in the art.
[0047] In the method for preparing a diaphragm of the present invention, the descriptions about the thickness of the layer, the composition of the layer, the material selection, etc. are the same as those described above and will not be repeated here.
[0048] Another aspect of the present invention relates to a lithium battery, which includes the above-mentioned separator.
[0049] In addition to the above-mentioned diaphragm, the lithium battery may have a conventional structure and components of a lithium battery in the art, for example, it may also include a negative electrode, a positive electrode, an electrolyte, and an aluminum-plastic film. There are no special restrictions on the negative electrode, the positive electrode, the electrolyte, and the aluminum-plastic film, and any negative electrode, positive electrode, electrolyte, and aluminum-plastic film known in the art that can be used for lithium batteries may be used. For example, the negative electrode may include a negative electrode sheet and a negative electrode active material layer coated on the negative electrode sheet; the positive electrode may include a positive electrode sheet and a positive electrode active material layer coated on the positive electrode sheet; the electrolyte may be one or more of carbonate, olefin carbonate, and carboxylate electrolytes. In addition, there are no special restrictions on the structure and assembly method of the lithium battery, and any structure and assembly method known in the art that can be used for lithium batteries may be used.
[0050] In one embodiment, the lithium battery includes: a positive electrode sheet provided with a positive electrode active material layer, the above-mentioned separator, a negative electrode sheet provided with a negative electrode active material layer, and an electrolyte.
[0051] In one embodiment, the positive electrode sheet is aluminum foil with a thickness of 8 to 15 μm, such as 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, etc.; the negative electrode sheet is copper foil with a thickness of 5 to 20 μm, such as 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, etc. .
[0052] The present invention has been described in detail above, but the above embodiments are only illustrative in nature and are not intended to limit the present invention. In addition, this article is not limited by any theory described in the above prior art or invention content or the following examples.
[0053] Unless otherwise expressly stated, the numerical ranges throughout the application documents include any sub-ranges therein and any numerical values incremented by the smallest sub-unit of a given value therein. Unless otherwise expressly stated, the numerical values throughout the application documents represent approximate measurements or limitations of the range of embodiments including slight deviations from the given values and having approximately the values mentioned and having the exact values mentioned. Except for the working examples provided at the end of the detailed description, all numerical values of the parameters (e.g., quantities or conditions) in the present application documents (including the appended claims) should be understood in all cases as being modified by the term "approximately", regardless of whether "approximately" actually appears before the numerical value. "Approximately" means that the numerical value described allows for slight imprecision (some close to precision in the value; approximately or reasonably close to the value; approximately). If the imprecision provided by "approximately" is not understood in this art with this common meaning, the "approximately" used herein at least represents the changes that can be produced by ordinary methods of measuring and using these parameters. For example, “about” can include a variation of less than or equal to 10%, less than or equal to 5%, less than or equal to 4%, less than or equal to 3%, less than or equal to 2%, less than or equal to 1%, or less than or equal to 0.5%, and in some aspects, a variation of less than or equal to 0.1%.
[0054] Unless otherwise expressly stated, the terms "comprising", "including", "having", "containing" or any other similar terms throughout the application documents are open-ended terms, which indicate that a composition or product may include, in addition to the elements listed herein, other elements that are not explicitly listed but are generally inherent to the composition or product. In addition, in this document, the terms "comprising", "including", "having", "containing" should be interpreted as specifically disclosed and also include closed or semi-closed conjunctions such as "consisting of" and "consisting essentially of". "Consisting essentially of" means that the elements listed herein account for more than 95%, more than 97%, or in some aspects, more than 99% of the composition or product.
[0055] Beneficial Effects
[0056] The present invention further improves the thermal stability, wettability and safety of the diaphragm by coating a ceramic layer on both sides of the surface of the base film. In addition, the present invention reduces the interface resistance between the ceramic layer and the positive and negative electrode materials by coating a graphite layer on the outer surface of the ceramic layer, reduces the internal resistance of the battery, reduces the loss of lithium ions during the deintercalation process, and improves the battery charge and discharge cycle performance. In addition, due to the conductive properties of graphite itself, when the battery is subjected to external impact or short circuit, the graphite layer on the diaphragm will expand the power tolerance range, reduce the risk of explosion or fire, and improve the safety performance of the battery.
[0057] The present invention adopts the method of coating ceramic layers on both sides of the base film surface, which further improves the thermal stability of the diaphragm, thereby improving the safety of the lithium battery. The outer surface of the ceramic is coated with a graphite layer to form a composite diaphragm, the process is simple, and the resulting composite diaphragm is softer than the negative electrode sheet, which has the advantages of avoiding the graphite layer from falling off and making the battery cell easier to form. In addition, the ceramic composite diaphragm provides a larger lithium insertion space for the negative current collector, and can be used as a lithium storage buffer during high current discharge, avoiding the loss of lithium ions caused by the irreversible formation of lithium dendrites. BRIEF DESCRIPTION OF THE DRAWINGS
[0058] Figure 1 is a schematic diagram of a separator according to one embodiment of the present invention.
[0059] Reference numerals:
[0060] 1: base film; 2, 3: first and second ceramic layers; 4, 5: first and second graphite layers DETAILED DESCRIPTION
[0061] The technical scheme of the present invention is further illustrated by the following examples. It should be understood by those skilled in the art that the examples are only used to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0062] Reagents and instruments
[0063] Unless otherwise specified, all materials and reagents used are commercially available products commonly used in the production of lithium battery related materials. Artificial graphite was purchased from Jiangxi Zichen Technology Co., Ltd. Polyvinylidene fluoride was purchased from Dongguan Liheng Plastic Raw Materials Co., Ltd. Styrene-butadiene latex, styrene-acrylic latex and polymethyl methacrylate were provided by Ningde Zhuogao New Materials Technology Co., Ltd. Conductive carbon black was purchased from Tianjin Tianyi Century Chemical Products Technology Development Co., Ltd. Lithium iron phosphate was purchased from Guizhou Anda Technology Energy Co., Ltd. Planetary stirring was carried out using a DJ200 planetary mixer manufactured by Shenzhen Xinjiatuo Automation Technology Co., Ltd.
[0064] Preparation Example: Preparation of positive electrode sheet containing positive electrode active material
[0065] 1.5g of polyvinylidene fluoride and 65g of N-methylpyrrolidone (NMP) were mixed and stirred evenly, and then 31.5g of lithium iron phosphate, a positive electrode material, and 2.0g of conductive carbon black were added to the glue solution. The mixture was dispersed at high speed for 3 hours at a vacuum degree of -0.08Mpa, a revolution of 25rpm / min, and a rotation of 2500rpm / min. Finally, the stirred slurry was defoamed in vacuum, sieved, and coated on aluminum foil, dried, and then pressed to a compact density of 3.75g / cm 3 The electrode sheet is rolled and finally slit and sliced to obtain the positive electrode of the lithium battery.
[0066] Example 1
[0067] 1) 36 g of styrene-butadiene latex with a solid content of 50% and 187 g of deionized water were mixed, stirred at 30° C. and 1000 rpm / min for 1 h, 170 g of alumina with a D50 of 1.5 μm and 100 g of a 5% CMC premixed solution were added, and stirring was continued for 1.5 h under the same conditions, and then 2 g of polyoxyethylene alkylamine was added, and stirring was continued at the same temperature and 500 rpm / min for 0.5 h to obtain a water-based ceramic slurry;
[0068] 2) 160 g of graphite with a D50 of 20 μm, 30 g of styrene-butadiene latex with a solid content of 50%, 80 g of a CMC premix solution with a concentration of 5%, and 285 g of deionized water were mixed and planetarily stirred at a temperature of 30° C., a speed of 1500 rpm / min, and a time of 2 h; then 2 g of conductive carbon black was added, the temperature was maintained at 30° C., and stirring was performed at 1000 rpm / min for 0.5 h to obtain an aqueous graphite slurry;
[0069] 3) coating the aqueous ceramic slurry described in 1) on both sides of the PE base film by micro-gravure coating, and drying to obtain a ceramic layer, the thickness of the layer on both sides is 3 μm;
[0070] 4) coating the aqueous graphite slurry described in 2) on the outer surface of the ceramic layer, drying to obtain a graphite layer, wherein the thickness of the graphite layer on both sides is 40 μm; and rolling up to obtain a ceramic composite diaphragm.
[0071] 5) The positive electrode prepared in the preparation example, the above-mentioned ceramic composite diaphragm, and the copper foil containing the double-sided graphite layer are wound into a square battery cell, put into a shell and baked, and after vacuum removal of moisture, an electrolyte (an organic electrolyte containing 1 mol / L LiPF6, wherein the solvent is ethylene carbonate: diethyl carbonate: dimethyl carbonate: ethylene carbonate = 1:1:1:1) is injected into the shell and sealed.
[0072] Example 2
[0073] 1) 36 g of styrene acrylic latex with a solid content of 50% and 187 g of deionized water were mixed, stirred at 30° C. and 1000 rpm / min for 0.5 h, 170 g of magnesium hydroxide with a D50 of 1.5 μm and 100 g of a 5% CMC premixed solution were added, stirred at 30° C. and 1500 rpm / min for 2 h, and then 2 g of polyoxyethylene alkylamine was added, and stirred at the same temperature and 800 rpm / min for 0.5 h to obtain a water-based ceramic slurry;
[0074] 2) 160 g of 20 μm graphite with a D50, 30 g of 50% solid content styrene acrylic latex, 80 g of 5% CMC premix solution, and 285 g of deionized water were mixed and planetarily stirred at a temperature of 35° C., a speed of 1500 rpm / min, and a time of 2 h; then 2 g of conductive carbon black was added, and the temperature was maintained at 35° C. and stirred at 1000 rpm / min for 1 h to obtain an aqueous graphite slurry;
[0075] 3) coating the aqueous ceramic slurry described in 1) on both sides of the PE base film by micro-gravure coating, and drying to obtain a ceramic layer, the thickness of the layer on both sides is 3.5 μm;
[0076] 4) coating the aqueous graphite slurry described in 2) on the outer surface of the ceramic layer, drying to obtain a graphite layer, wherein the thickness of the graphite layer on both sides is 35 μm; and rolling up to obtain a ceramic composite diaphragm.
[0077] 5) The positive electrode prepared in the preparation example, the above-mentioned ceramic composite diaphragm, and the copper foil containing the double-sided graphite layer are wound into a square battery cell, put into a shell and baked, and after vacuum removal of moisture, an electrolyte (an organic electrolyte containing 1 mol / L LiPF6, wherein the solvent is ethylene carbonate: diethyl carbonate: dimethyl carbonate: ethylene carbonate = 1:1:1:1) is injected into the shell and sealed.
[0078] Example 3
[0079] 1) 36 g of polymethyl methacrylate with a solid content of 50% and 187 g of deionized water were mixed, stirred at 30° C. and 1500 rpm / min for 1 h, 170 g of boehmite with D50=1.0 μm and 100 g of a 5% CMC premixed solution were added, stirred at 30° C. and 1500 rpm / min for 2 h, and then 2 g of ethylene oxide alkylamine was added, and stirred at the same temperature and 1000 rpm / min for 0.5 h to obtain a water-based ceramic slurry;
[0080] 2) 160 g of 20 μm graphite with a D50, 15 g of polymethyl methacrylate, 80 g of a 5% CMC premix solution, and 300 g of deionized water were mixed and planetarily stirred at a temperature of 40° C., a speed of 2000 rpm / min, and a time of 2 h; then 2 g of acetylene black was added, and the temperature was maintained at 40° C. and stirred at 1500 rpm / min for 1 h to obtain an aqueous graphite slurry;
[0081] 3) coating the aqueous ceramic slurry described in 1) on both sides of the PE base film by micro-gravure coating, and drying to obtain a ceramic layer, the thickness of the layer on both sides is 2.5 μm;
[0082] 4) coating the aqueous graphite slurry described in 2) on the outer surface of the ceramic layer, drying to obtain a graphite layer, wherein the thickness of the graphite layer on both sides is 45 μm; and rolling up to obtain a ceramic composite diaphragm.
[0083] 5) The positive electrode prepared in the preparation example, the above-mentioned ceramic composite diaphragm, and the copper foil containing the double-sided graphite layer are wound into a square battery cell, put into a shell and baked, and after vacuum removal of moisture, an electrolyte (an organic electrolyte containing 1 mol / L LiPF6, wherein the solvent is ethylene carbonate: diethyl carbonate: dimethyl carbonate: ethylene carbonate = 1:1:1:1) is injected into the shell and sealed.
[0084] Example 4
[0085] 1) 36 g of polyacrylonitrile with a solid content of 50% and 187 g of deionized water were mixed, stirred at 35° C. and 2000 rpm / min for 1.5 h, then titanium oxide with a D50 of 1.5 μm and 100 g of a 5% CMC premixed solution were added, stirred at 35° C. and 1500 rpm / min for 1.5 h, then 2 g of polyoxyethylene alkylamine was added, and stirred at the same temperature and 500 rpm / min for 1 h to obtain a water-based ceramic slurry;
[0086] 2) 160 g of 20 μm graphite with a D50, 15 g of polyvinylidene fluoride, 80 g of a 5% CMC premix solution, and 300 g of deionized water were mixed and planetarily stirred at a temperature of 30° C., a speed of 2500 rpm / min, and a time of 2.5 h; then 2 g of acetylene black was added, and the temperature was maintained at 30° C. and stirred at 1500 rpm / min for 0.5 h to obtain an aqueous graphite slurry;
[0087] 3) coating the aqueous ceramic slurry described in 1) on both sides of the PE base film by micro-gravure coating, and drying to obtain a ceramic layer, the thickness of the layer on both sides is 3 μm;
[0088] 4) coating the aqueous graphite slurry described in 2) on the outer surface of the ceramic layer, drying to obtain a graphite layer, wherein the thickness of the graphite layer on both sides is 40 μm; and rolling up to obtain a ceramic composite diaphragm.
[0089] 5) The positive electrode prepared in the preparation example, the above-mentioned ceramic composite diaphragm, and the copper foil containing the double-sided graphite layer are wound into a square battery cell, put into a shell and baked, and after vacuum removal of moisture, an electrolyte (an organic electrolyte containing 1 mol / L LiPF6, wherein the solvent is ethylene carbonate: diethyl carbonate: dimethyl carbonate: ethylene carbonate = 1:1:1:1) is injected into the shell and sealed.
[0090] Example 5
[0091] 1) 36 g of polyacrylonitrile with a solid content of 50% and 187 g of deionized water were mixed, stirred at 30° C. and 1000 rpm / min for 0.5 h, alumina with a D50 of 1.5 μm and 100 g of a 5% CMC premixed solution were added, stirred at 30° C. and 1500 rpm / min for 2 h, and then 2 g of polyoxyethylene alkylamine was added, and stirred at the same temperature and 500 rpm / min for 1 h to obtain a water-based ceramic slurry;
[0092] 2) 160 g of 20 μm graphite with a D50, 15 g of polyvinylidene fluoride, 80 g of a 5% CMC premix solution, and 300 g of deionized water were mixed and planetarily stirred at a temperature of 30° C., a speed of 2500 rpm / min, and a time of 2.5 h; then 2 g of acetylene black was added, and the temperature was maintained at 30° C. and stirred at 1500 rpm / min for 0.5 h to obtain an aqueous graphite slurry;
[0093] 3) coating the aqueous ceramic slurry described in 1) on both sides of the PE base film by micro-gravure coating, and drying to obtain a ceramic layer, the thickness of the layer on both sides is 3 μm;
[0094] 4) coating the aqueous graphite slurry described in 2) on the outer surface of the ceramic layer, drying to obtain a graphite layer, wherein the thickness of the graphite layer on both sides is 45 μm; and rolling up to obtain a ceramic composite diaphragm.
[0095] 5) The positive electrode prepared in the preparation example, the above-mentioned ceramic composite diaphragm, and the copper foil containing the double-sided graphite layer are wound into a square battery cell, put into a shell and baked, and after vacuum removal of moisture, an electrolyte (an organic electrolyte containing 1 mol / L LiPF6, wherein the solvent is ethylene carbonate: diethyl carbonate: dimethyl carbonate: ethylene carbonate = 1:1:1:1) is injected into the shell and sealed.
[0096] Comparative Example
[0097] 1) 36 g of styrene-butadiene latex with a solid content of 50% and 187 g of deionized water were mixed, stirred at 30° C. and 1000 rpm / min for 1 h, 170 g of alumina with a D50 of 1.5 μm and 100 g of a 5% CMC premixed solution were added, and stirring was continued for 1.5 h under the same conditions, and then 2 g of polyoxyethylene alkylamine was added, and stirring was continued at the same temperature and 500 rpm / min for 0.5 h to obtain a water-based ceramic slurry;
[0098] 2) 160 g of graphite with a D50 of 20 μm, 30 g of styrene-butadiene latex with a solid content of 50%, 80 g of a CMC premix solution with a concentration of 5%, and 285 g of deionized water were mixed and planetarily stirred at a temperature of 30° C., a speed of 1500 rpm / min, and a time of 2 h; then 2 g of conductive carbon black was added, the temperature was maintained at 30° C., and stirring was performed at 1000 rpm / min for 0.5 h to obtain an aqueous graphite slurry;
[0099] 3) coating the aqueous ceramic slurry described in 1) on both sides of the PE base film by micro-gravure coating, and drying to obtain a ceramic layer, the thickness of the layer on both sides is 3 μm;
[0100] 4) coating the aqueous graphite slurry described in 2) on both sides of the negative electrode sheet, drying to obtain a graphite layer with a thickness of 40 μm; rolling, slitting and sheeting to obtain a negative electrode sheet containing a negative electrode active material.
[0101] 5) The positive electrode, ceramic diaphragm, and negative electrode sheet containing negative electrode active material prepared in the preparation example are wound into a square battery cell, placed in a shell and baked, and after vacuum removal of moisture, an electrolyte (an organic electrolyte containing 1 mol / L LiPF6, wherein the solvent is ethylene carbonate: diethyl carbonate: dimethyl carbonate: ethylene carbonate = 1:1:1:1) is injected into the shell and sealed.
[0102] Experimental Example 1
[0103] The base film and ceramic diaphragm samples of Examples 1 to 5 and the comparative example were placed in an oven at 105°C and 130°C for heat shrinkage measurement for 1 hour. The sample size was 100mm×200mm. The test results are shown in Table 1 below:
[0104] Table 1 Thermal shrinkage of base film / ceramic coating (%)
[0105]
[0106] It can be seen from the results in Table 1 that there is no significant difference in shrinkage between the embodiment and the comparative example.
[0107] Experimental Example 2
[0108] The batteries of Examples 1-5 and the comparative example were subjected to nail penetration test (4.3V high voltage battery). The experimental results are compared as shown in Table 2 below:
[0109] Table 2
[0110]
[0111] As can be seen from Table 2, neither Examples 1-5 nor the comparative example ignited, smoked, or exploded during the nail penetration test, but the peak temperature of the comparative example was significantly higher than that of Examples 1-5. The reason may be that the graphite layer on the diaphragm in Examples 1-5 expanded the range of power tolerance during short circuit, reduced the risk of explosion or fire, and improved the safety performance of the battery.
[0112] Experimental Example 3
[0113] The battery packs of Examples 1-5 and the comparative example (including 5 batteries) were taken and the cycle performance test was performed after full charge. The lithium-ion battery was charged at a rate of 1C and discharged at a rate of 1C at room temperature for 500 cycles, and the battery capacity before and after each cycle was recorded (the average value of 5 battery data was taken for each group). The capacity retention rate after n cycles = (battery capacity after n cycles / battery capacity before cycles) × 100%. The capacity retention rate after 500 cycles is shown in Table 3:
[0114] Table 3
[0115] project Example 1 Example 2 Example 3 Example 4 Example 5 Comparative Example Capacity retention rate % 96.51% 96.13% 95.78% 96.33% 95.45% 90.45%
[0116] It can be seen from the results in Table 3 that the capacity retention rate of the embodiment is improved compared with the comparative example.
Claims
1. A diaphragm, include: Basement membrane; A first and a second ceramic layer are disposed on both surfaces of the base film, wherein the first and the second ceramic layers each independently comprise ceramic particles, a binder, a thickener and a wetting agent, wherein, based on the total weight of the ceramic layer, the content of the ceramic particles is 60-90wt%, the content of the binder is 5-25wt%, the content of the thickener is 4-10wt%, the content of the wetting agent is 0.01-5wt%, and the thickness of the first and the second ceramic layers is each independently 0.5-10μm; and First and second graphite layers are arranged on the outer surfaces of the first and second ceramic layers, wherein the first and second graphite layers each independently include graphite, a binder, a thickener and a conductive agent, wherein, based on the total weight of the graphite layer, the content of graphite is 60~95wt%, the content of the binder is 4~30wt%, the content of the conductive agent is 0.5~2wt%, the content of the thickener is 0.5~10wt%, and the thickness of the first and second graphite layers is each independently 0.1~50μm.
2. The diaphragm according to claim 1, in, The base film is a microporous film, a porous film or a non-woven film; and / or The base film has a pore size of 0.01 to 0.1 μm and a porosity of 20% to 80%; and / or The base film has a thickness of 30 μm or less.
3. The diaphragm according to claim 2, in, The microporous membrane and the porous membrane are polyolefin membranes; and / or The base film has a thickness of 3-20 μm.
4. The diaphragm according to claim 1, in, Based on the total weight of the ceramic layer, the content of the ceramic particles is 70-85wt%, the content of the binder is 9-15%, the content of the thickener is 5-8wt%, and the content of the wetting agent is 0.01%-2wt%.
5. The diaphragm according to claim 1, in, The first and second ceramic layers are each independently a water-based ceramic layer formed by preparing ceramic layer components into a water-based ceramic slurry, coating the slurry on the base film, and then drying the slurry, wherein the solid content of the slurry is 10-70wt%.
6. The diaphragm according to claim 1, in, The thickness of the first and second ceramic layers is independently 2-5 μm.
7. The diaphragm according to claim 1, in, The particle size of the ceramic particles is 0.1-5 μm.
8. The diaphragm according to claim 1, in, The ceramic particles are one or more selected from the group consisting of aluminum oxide, titanium oxide, magnesium oxide, magnesium hydroxide and boehmite.
9. The diaphragm according to claim 1, in, Based on the total weight of the graphite layer, the content of graphite is 75-85wt%, the content of the binder is 8-20wt%, the content of the conductive agent is 0.5-1.5wt%, and the content of the thickener is 2-6wt%.
10. The diaphragm according to claim 1, in, The first and second graphite layers are each independently a water-based graphite layer formed by preparing graphite layer components into a water-based graphite slurry, coating the slurry on the ceramic layer, and then drying the slurry. The solid content of the slurry is 20-60wt%.
11. The diaphragm according to claim 1, in, The thickness of the first and second graphite layers is independently 20-40 μm.
12. A method for preparing a separator according to any one of claims 1 to 11, The following steps are involved: 1) Mix ceramic particles, binder, wetting agent and deionized water to obtain water-based ceramic slurry. 2) Mix graphite, binder, conductive agent and deionized water evenly to obtain water-based graphite slurry. 3) coating the aqueous ceramic slurry on both surfaces of the base film to form the first and second ceramic layers and then drying; 4) The aqueous graphite slurry is applied onto the outer surfaces of the first and second ceramic layers to form the first and second graphite layers, respectively, and dried to obtain a separator.
13. The method according to claim 12, in, Step 1) is performed as follows: ceramic particles and deionized water are mixed, stirred at 20-40°C and a speed of 500-3000 rpm / min for 0.5-2 hours, a binder is added, and stirring is continued for 0.5-1.5 hours under the same conditions, and then a wetting agent is added, and stirring is continued for 0.5-1 hour at the same temperature and 300-800 rpm to obtain a water-based ceramic slurry; and / or Step 2) is carried out as follows: graphite, binder and deionized water are mixed and planetarily stirred at a temperature of 25-40°C, a rotation speed of 1000-2500 rpm / min, and a time of 0.5-2h; then a conductive agent is added, and the temperature is maintained at 25-40°C, and the stirring is performed at 800-2000 rpm / min for 20min-1.5h to obtain an aqueous graphite slurry.
14. A lithium battery comprising the separator according to any one of claims 1 to 11.
15. The lithium battery according to claim 14, include: A positive electrode sheet provided with a positive electrode active material layer, a separator according to any one of claims 1 to 11, a negative electrode sheet provided with a negative electrode active material layer, and an electrolyte.
16. The lithium battery according to claim 15, in, The positive electrode sheet is aluminum foil with a thickness of 8 to 15 μm; the negative electrode sheet is copper foil with a thickness of 5 to 20 μm.
Citation Information
Patent Citations
Ceramic composite diaphragm and lithium cell that contain graphite layer
CN208460854U
Separators for high density electrochemical energy storage
WO2017160897A1
